Intergenerational Mobility Trends and the Changing Role of Female Labor - Ulrika Ahrsjö; René Karadakic; Joachim Kahr Rasmussen (University of Copenhagen, Department of Economics, Center for Economic Behavior and Inequality (CEBI), 2021)
We present new evidence on the existence and drivers of trends in intergenerational income mobility using administrative income data from Scandinavia along with survey data from the United States. Harmonizing the data from Sweden, Denmark and Norway, we first find that intergenerational rank associations in income have increased uniformly across Scandinavia for cohorts of children born between 1951 and 1979. These trends are robust to a large set of empirical specifications that are common in the associated literature. However, splitting the trends by gender, we find that father-son mobility has been stable in all three countries, while correlations involving females display substantial trends. Similar patterns are confirmed in the US data, albeit with slightly different timing. Utilizing information about individual occupation, education and income in the Scandinavian data, we find that intergenerational mobility in latent economic status has remained relatively constant for all gender combinations. This suggests that a gradual reduction in gender-specific labor market segregation, increased female labor force participation and increased female access to higher education has strengthened the signal value that maternal income carries about productivity passed on to children. Based on these results, we argue that the observed decline in intergenerational mobility in Scandinavia is consistent with a socially desirable development where female skills are increasingly valued at the labor market, and that the same is likely to be true also in the US.
Keywords: J62; J21; 330; Intergenerational Mobility; Labor Force Participation